Armenia And Finland: Early Contacts - Bakhchinyan, Artsvi; Karttunen, Klaus (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Finland unlike many other Western nations does not have longtime relations with the Armenian people. Nevertheless, it is more than 300 years that the Finns and Armenians know each other to a certain extent; moreover, some Finnish scholars have been interested in various fields of the Armenian reality . Over centuries the Armenians had only sporadic historical and cultural contacts with the Nordic states of Norway, Denmark, Sweden and Finland. Interestingly, in the 19th century, both Finland and Eastern Armenia, geographically so far from each other, were parts of the Russian Empire, thus, the two peoples were in the same administrative system for over a hundred years . Հայ և ֆինն ժողովուրդների պատմական ուղիներն անցած երեք դարերի ընթացքում հատվել են տարբեր համատեքստերում, հատկապես՝ Ֆինլանդիայում արևելագիտության զարգացման առնչությամբ: Исторические пути армянского и финского народов пересекались за последние три столетия в разных контекстах, особенно в развитии востоковедения в Финляндии. Армяно-финские отношения представлены в пяти эпизодах.
Keywords: History